THE ROLE OF WORKING MEMORY IN LANGUAGE PROCESSING IN MULTILINGUAL INDIVIDUALS - Simarmata, Pika Marselli; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study explores multilingual abilities and their impact on sentence comprehension and production. The ability to master more than one language (multilingualism) is known to provide various cognitive benefits, including in language processing. This study reviews how multilingual individuals process and comprehend sentences in the various languages they master, as well as how they produce sentences in those languages. Through experimental methods and neurocognitive analysis, this research finds that multilingual individuals exhibit higher cognitive flexibility, better working memory capacity, and more efficient language management abilities compared to monolingual individuals. The results of this study provide in-depth insights into the cognitive mechanisms underlying multilingual abilities and their implications in educational and clinical contexts.